The development of problem-solving of grade 11 students using problem-based learning integrated with questioning strategies - Chomsriharat, Siriphit; Polyiem, Titiworada (Journal of Green Learning, 2024)
This study examined the effects of problem-based learning (PBL) integrated with questioning strategies on the problem-solving of 19 grade 11 students in the Thai educational context. Participants were selected using a purposive sampling method. The study was developed in an action research. It involved three learning cycles, each encompassing the stages of planning, action, observation, and reflection. The instruments used in the study included a learning management plan designed with PBL and questioning strategies, a problem-solving thinking test, interviews, and observation forms.The data were analyzed using percentage, mean score, and standard deviation. The results indicated that the instructional method had positive effects on the participants' knowledge, thinking skills, and attitudes toward science learning. The findings suggest that integrating PBL with questioning strategies can effectively enhance student engagement and cognitive abilities in science education.